Marketingový mix podniku - Tefferová, Iva (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Tématem této bakalářské práce je ,,Marketingový mix společnosti SKITECH, s. r. o.“ Práce se zabývá vypracováním marketingového mixu a navrţením lyţařských produktů skiareálu. Předpokladem pro vytvoření marketingového mixu je provedení SWOT analýzy a analýzy konkurence. Na základě těchto výsledků budou stanoveny vize a cíle skiareálu a návrhy jednotlivých produktů. V závěrečné části je aplikován marketingový mix na konkrétní produkt.

This thesis deals with the marketing mix of the SKITECH company. The thesis focuses on developing a marketing mix and proposing ski products of ski resort. A prerequisite for the creation of a marketing mix is the SWOT analysis and competitor analysis. Based on these results, it establish the vision and objectives of ski resort and propose different products. In final part of the marketing mix it apply them to a specific product.
Company Marketing Mix
Keywords: Marketing; marketingový mix; produkt; cena; distribuce; propagace; SWOT analýza; skiareál; Marketing; marketing mix; product; price; place; promotion; SWOT analysis; ski resort